TEACHER TALK AROUND THE TEXT: EXPLORING GENDER IDEOLOGY OF PRE-SERVICE TEACHER IN EFL CLASSROOM - Rahayu, Yustika (2017)
Research of gender and teaching materials have been focused solely on texts, an exploration of teacher behavior in relation to texts or "teacher talk around the text" have been missed. The research is aimed at investigating the ways pre-service teacher's gender ideology manifested in the talks around gendered texts. It also explored the topic of gender, in relation to classroom interaction. The research used descriptive qualitative approach while in collecting the data the instrument used were FLINT System and Gendered Discursive Practices. The data were traced from the collected and categorized data in pre-service teacher's transcriptions of classroom observations, interviews and field notes of the observer. The manifestation of the pre-service teacher's gender ideologies were presented in a form of pre-service teacher's consumption or mediation of the text, which play role in shaping student response and, by extension, gender ideologies. The data shows cases of "traditional" focus of text being ignored, "progressive" texts being undermined. Those parts of texts that can be seen as Gender Critical Points also ignored and talk about gender issues within texts being characterized by gender blindness. Although the teacher tried to trigger gender discussion by asking questions, the teacher still mostly used display questions. It was observed that referential questions made more classroom interactions. Thus, it is recommended that teacher should use more referential questions in attempt to elicit long answers through higher- level thinking questions.----------Penelitian dengan topik gender dan materi pengajaran hanya terfokus pada teks. Satu hal yang nampaknya telah dilewatkan adalah eksplorasi perilaku guru dalam kaitannya dengan teks, apa yang bisa kita sebut "tuturan guru seputar teks", yang sebenarnya tidak dapat diprediksi. Dengan demikian, penelitian ini bertujuan untuk menyelidiki bagaimana ideologi gender guru PPL terwujud dalam pembicaraan seputar teks gender. Hal ini juga menjelajahi topik gender, dalam kaitannya dengan interaksi kelas. Penelitian ini menggunakan pendekatan deskriptif kualitatif. Data penelitian ditelusuri dari data yang dikumpulkan dan dikategorikan dalam transkrip observasi kelas pra-layanan guru, wawancara dan catatan lapangan pengamat. Manifestasi dari ideologi gender guru PPL disajikan dalam bentuk praktik diskursif gender sebagai konsumsi guru PPL atau mediasi dari teks, yang memainkan peran dalam membentuk respon siswa dan juga ideologi gender. Data menunjukkan bahwa teks "tradisional" diabaikan, teks "progresif" diruntuhkan, bagian teks yang dapat dilihat mengandung Poin Kritis Gender diabaikan, dan membicarakan isu gender dalam teks yang ditandai dengan kebutaan gender. Meskipun guru mencoba untuk memicu diskusi gender dengan mengajukan pertanyaan, dia masih banyak digunakan pertanyaan display. Meskipun tampaknya para guru dapat mendorong pelajar bahasa dan memberi mereka masukan yang dapat dipahami melalui penggunaan pertanyaan display, diamati bahwa pertanyaan referensial membuat lebih banyak interaksi kelas. Dengan demikian, disarankan bahwa guru menggunakan lebih banyak pertanyaan referensial dalam upaya memperoleh jawaban panjang melalui pertanyaan tingkat berpikir lebih tinggi.